2021
DOI: 10.1039/d0tb02547j
|View full text |Cite
|
Sign up to set email alerts
|

Chemodynamic/photothermal synergistic therapy based on Ce-doped Cu–Al layered double hydroxides

Abstract: The combination of chemodynamic therapy (CDT) with photothermal therapy (PTT) is an efficacious strategy in cancer treatment to acquire satisfactory therapy efficiency under endogenous redox reaction and external laser induction....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 60 publications
0
38
0
Order By: Relevance
“…In addition, other metal elements have also been exploited for realizing two‐metal‐ion‐based CDT. [ 371–388 ] Yang et al. designed ancient pigment nanosheets (SrCuSi 4 O 10 NSs, abbreviated as SC NSs) and functionalized them with GOx to afford SC@G NSs for the synergistic action of ST, PTT, and CDT ( Figure a).…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other metal elements have also been exploited for realizing two‐metal‐ion‐based CDT. [ 371–388 ] Yang et al. designed ancient pigment nanosheets (SrCuSi 4 O 10 NSs, abbreviated as SC NSs) and functionalized them with GOx to afford SC@G NSs for the synergistic action of ST, PTT, and CDT ( Figure a).…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…constructed Ce‐doped Cu–Al layered double hydroxide (CAC‐LDH) ultrathin nanosheets through a bottom‐up synthetic method, which were further loaded with ICG to obtain ICG/CAC‐LDH composite. [ 379 ] First, Cu 2+ and Ce 4+ of ICG/CAC‐LDH could be reduced by intracellular GSH to Cu + and Ce 3+ , respectively, leading to the GSH depletion. The produced Cu + and Ce 3+ could further react with local H 2 O 2 to generate •OH through the Fenton‐like reactions.…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…This result was achieved due to the enhanced cell membrane permeability and increased uptake of doxorubicin. Recently, Wang et al described a novel modality combining chemodynamic therapy (CDT) with PTT 124 . The results from in vitro studies showed remarkable CDT/PTT efficacy, with complete apoptosis of the cancer cells.…”
Section: Sonodynamic Therapymentioning
confidence: 99%
“…Further, the coordinating hydroxide groups can be protonated, providing a pH-responsive property which can be utilized in cancer diagnosis and treatment. A number of Gd-doped LDHs have been developed as multifunctional platforms for both bioimaging and treatment [22][23][24]. Other ions have also been explored.…”
Section: Introductionmentioning
confidence: 99%